Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/es103333j
|View full text |Cite
|
Sign up to set email alerts
|

Dechlorane Plus and Related Compounds in Peregrine Falcon (Falco peregrinus) Eggs from Canada and Spain

Abstract: Concentrations of Mirex, Dechlorane (Dec) Plus (DP), Dec 602, Dec 603, and Dec 604 were significantly higher in peregrine falcon (Falco peregrinus) eggs from Canada than Spain, with the former having the only measurable concentrations of the dechlorinated DP products, decachloropentacyclooctadecadiene (aCl10DP) and undecachloropentacyclooctadecadiene (aCl11DP). Large variations also occurred in the in ovo concentrations of the DP monoadduct, DPMA. This is the first study to report the accumulation and metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 21 publications
7
98
4
1
Order By: Relevance
“…DP isomeric composition in hen eggs has not been reported so far. Our f anti values were in the range of the ratios reported in white stork eggs from an urban (in average of 0.66) and industrial colony (0.64) in Spain (Muñoz-Arnanz et al, 2011), herring gull eggs from the Laurentian Great Lakes (0.69) (Gauthier and Letcher, 2009), and peregrine falcon eggs from Canada (0.58) and Spain (0.77) (Guerra et al, 2011).…”
Section: E-waste Recycling Sitessupporting
confidence: 61%
“…DP isomeric composition in hen eggs has not been reported so far. Our f anti values were in the range of the ratios reported in white stork eggs from an urban (in average of 0.66) and industrial colony (0.64) in Spain (Muñoz-Arnanz et al, 2011), herring gull eggs from the Laurentian Great Lakes (0.69) (Gauthier and Letcher, 2009), and peregrine falcon eggs from Canada (0.58) and Spain (0.77) (Guerra et al, 2011).…”
Section: E-waste Recycling Sitessupporting
confidence: 61%
“…Thereafter, different levels of DP were obtained in various biota samples including the human body (Barón et al, 2014a;Gauthier and Letcher, 2009;Guerra et al, 2011;Ren et al, 2009;Salamova and Hites, 2013;Sun et al, 2012;Wu et al, 2010), confirming bioavailability of DP in both the terrestrial and aquatic biotas. Chemicals were considered to be bioaccumulative if the bioaccumulation factor (BAF) was greater than 5000 (Kelly et al, 2007), corresponding to a logBAF of 3.70.…”
Section: Bioaccumulation and Biomagnification Potentialmentioning
confidence: 81%
“…Therefore, these two hypotheses are still needed to be confirmed. DP dechlorination products were commonly reported in biota including human tissues, the levels were generally much lower than those of DP (Ben et al, 2013;Chen et al, 2011Chen et al, , 2013aGuerra et al, 2011;Mo et al, 2013;Muñoz-Arnanz, et al, 2011Peng et al, 2012Peng et al, , 2014Sun et al, 2012;Yan et al, 2012;Zhang et al, 2011b;Zheng et al, 2010Zheng et al, , 2014. However, an extremely high level was observed in a fresh water food web around DP facility in Huai'an, China, where the concentrations of anti-Cl 10 -DP and anti-Cl 11 -DP was 84.4 ng g −1 lw and 1030 ng g −1 lw, respectively .The dechlorinated products of DP in biota were mainly attributed to accumulation from the external habitat environment rather than internal metabolism, although the gender difference observed in some cases suggested that anti-Cl 11 -DP in the human body may be partly formed from in vivo dechlorination of the anti-isomer (Yan et al, 2012).…”
Section: Dp Dechlorinated Analogsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several DP dechlorinated analogs have been identified but not quantified in sediments from Lake Ontario and in human serum from an e-waste recycling site in South China (Ren et al, 2009). They were also detected in peregrine eggs from Canada (Guerra et al, 2011), white stork eggs from Spain (Muñoz-Arnanz et al, 2011), muscle and liver of several raptor species from China (Chen et al, 2013), and dust, air, plants, fish, and birds from the same e-waste recycling site as the present study Chen et al, 2011;Zhang et al, 2011b;Mo et al, 2013). While a number of studies have demonstrated the environmental presence and bioavailability of these dechlorination products, there is still a dearth of information on their sources and potential dechlorination pathways.…”
Section: Residue Levelsmentioning
confidence: 95%